Online durch Thailand – Mehrwert nicht nur für virtuelle Kontakter! Die Konzeption von Online-Exkursion und Online-Chat mit einem Feedback der teilnehmenden Lehrkräfte und Schulklassen - Schleicher, Yvonne (Zeitschrift für Geographiedidaktik (ZGD), 2005)
The Online-Excursions 2004 (Thailand) with its Online-Chat provided communication between a group of students in the field in Thailand and classes at schools in Germany. With reports posted to a website, schools could follow the excursion day by day. In a questionnaire at the end of the excursion, teachers and pupils gave a feedback about several items which are reported in the article: What is interesting for school-children about Thailand? How can an online-excursion manage to generate interest by combining reports about everyday life and geographical facts? What are the intentions and concepts of this Internet project? How did students and teachers at school use the Internet modules? What are the profits of this online project?